HOMOSEKSUAL DALAM PANDANGAN HUKUM ISLAM DAN HUKUM POSITIF INDONESIA - Choirun Nisa (Fakultas Hukum Universitas Tarumanagara, 2021)
Islamic law sees that sexual desire is a human nature given by Allah. Thus, Islamic law regulates the form of action to channel human biological desires with marriage. Islamic law prohibits any sexual act that is not in accordance with the nature and teachings of Islam, for example homosexuality. Homosexuality is an act that is forbidden and cursed by Allah. This act is clearly prohibited as stated in the Qur'an and Hadith. The opinions of the Ulama and the arguments of Islamic law have agreed to prohibit homosexual acts. This action will only cause losses such as venereal disease, oral cancer and others. From the arguments governing homosexuality, there are several arguments that say that homosexual perpetrators must be killed, punished, and even put in prison.